# Help me through a simple SR problem

## Main Question or Discussion Point

I'm reading Wheeler's spacetime physics and have been doing some newbie SR problems.
I thought up what shouldd be an extremely simple problem but am having trouble with the math, I'm sure one of you guys can probably help me out with it.

Events A and B occur with a time separation in the laboratory frame but no space separation, I thought it'd be easy to prove that in a rocket frame moving with a $$\beta$$ speed to the right relative to the laboratory frame the space separation divided by the time separation of the events would be $$-\beta$$ (that is $$dx'/dt'=-\beta$$)

$$dt^2-dx^2 = dt'^2-dx'^2$$

Since the events occur in the same place in the laboratory frame
$$dt^2 = dt'^2-dx'^2$$

After Lorentz transformation
$$( \frac{dt' + dx'\beta} { \sqrt{1-\beta^2}} )^2 = dt'^2-dx'^2$$

However, I've been unable to derive this properly, is it just lack of math skills or did I set the equations inproperly? Any help is appreciated.

Related Special and General Relativity News on Phys.org
George Jones
Staff Emeritus
Gold Member
Your last equation does lead to your desired result. First factor out $dt'^2$ from both sides of the last equation, and then solve for $dx'/dt'$.

I must suck at this, so far I have
$$( \frac{dt' + dx'\beta} { \sqrt{1-\beta^2}} )^2 = dt'^2-dx'^2$$

$$\frac{(dt' + dx'\beta)^2} {1-\beta^2} = dt'^2-dx'^2$$

$$(dt' + dx'\beta)^2 = (dt'^2-dx'^2) (1-\beta^2)$$

$$dt'^2 + 2dt'dx'\beta + dx'^2\beta^2 = dt'^2 - dt'^2\beta^2 -dx'^2 +dx'^2\beta^2$$

$$2dt'dx'\beta = -dt'^2\beta^2 -dx'^2$$

$$dx'^2 + dt'^2\beta^2 + 2dt'dx'\beta = 0$$

This does not seem to hold up when $$\frac{dx'}{dt'} = -\beta$$

Where am I screwing up?

Fredrik
Staff Emeritus
Gold Member
I posted this once already and deleted it because I incorrectly thought I had made a mistake, and the forum won't let me post a duplicate, so I had to add this pointless sentence.

Where am I screwing up?
Here:
This does not seem to hold up when $$\frac{dx'}{dt'} = -\beta$$

$$dx'^2 + 2dt'dx'\beta + dt'^2\beta^2 = 0$$

$$a = dt'\beta$$

thus
$$dx'^2 + 2adx' + a^2 = 0$$

$$(dx' + a)^2 = 0$$

$$dx' + a = 0$$

$$dx' = -a$$

$$dx' = -dt'\beta$$

$$dx'/dt' = -\beta$$

Thanks everyone, I will proceed and slap myself in the head so you won't have to